2004
DOI: 10.1021/jm030470e
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Non-Phosphate-Containing Small Molecular Weight Inhibitors of the Tyrosine Kinase p56 Lck SH2 Domain via in Silico Screening against the pY + 3 Binding Site

Abstract: The protein p56 lymphoid T cell tyrosine kinase (Lck) is predominantly expressed in T lymphocytes where it plays a critical role in T-cell-mediated immune response. Lck participates in phosphotyrosine-dependent protein-protein interactions through its modular binding unit, the Src homology-2 (SH2) domain. Accordingly, virtual screening methods combined with experimental assays were used to identify small molecular weight nonpeptidic compounds that block Lck SH2 domain-dependent interactions. Virtual screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 39 publications
2
75
0
Order By: Relevance
“…1A) for the initial CADD screen. A database of 1.5 million commercially available, low molecular weight chemicals was subjected to an in silico screen for molecules that may bind within the DNA-binding pocket using the program DOCK (6)(7)(8)(9)(10). From this virtual screen, a total of 233 compounds were selected for biochemical and biological assays.…”
Section: Resultsmentioning
confidence: 99%
“…1A) for the initial CADD screen. A database of 1.5 million commercially available, low molecular weight chemicals was subjected to an in silico screen for molecules that may bind within the DNA-binding pocket using the program DOCK (6)(7)(8)(9)(10). From this virtual screen, a total of 233 compounds were selected for biochemical and biological assays.…”
Section: Resultsmentioning
confidence: 99%
“…Although molecular docking screens of chemical databases are widely used for ligand discovery, [1][2][3][4][5][6][7] the method retains important weaknesses. [8][9][10][11][12][13] A testament to these is the criterion by which docking screens are evaluated: the enrichment of annotated ligands from among a large database of presumed non-binding, "decoy" molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, a high number of case studies has been reported using a variety of SBVS methods, demonstrating its broad applicability and the level of interest in this drug design strategy. Some important applications include, besides the examples abovementioned, the identification of antagonists of the thyroid hormone receptor, the discovery of inhibitors of tyrosine kinase p56 Lck, the selection of epidermal growth factor receptor (EGFR) inhibitors, as well as the discovery of inhibitors of the Bcl-2 protein [54][55][56][57]. The strategy for identification of ellagic acid, a natural compound, as nanomolar competitive inhibitor of casein kinase 2 (CK2), is depicted in Fig.…”
Section: Structure-based Virtual Screeningmentioning
confidence: 99%